The Value of Human and Social Capital Investments for the Business Performance of Start-ups - Niels Bosma; Mirjam van Praag; Roy Thurik; Gerrit de Wit (Tinbergen Institute, 2002)
We investigate the manifold posed question: To what extent does investment in human and social capital, besides the effect of talent, enhance entrepreneurial performance? We distinguish between three different performance measures: survival, profits, and generated employment. On the basis of the empirical analysis of a rich Dutch longitudinal data set of firm founders, we conclude that specific investments indeed affect the three performance measures substantially and significantly. Specific attention is paid to the unobserved talent bias. Moreover, the effect of the emergence of so called knowledge industries is explored.
Keywords: M13; D92; J24; 330; entrepreneurship; human capital; social capital; small business; start-ups; performance; Bildungsinvestition; Social Capital; Unternehmenserfolg; Unternehmensgründung; KMU; Niederlande